2017
DOI: 10.1093/humrep/dex331
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of melatonin in porcine oocyte meiotic failure caused by the exposure to benzo(a)pyrene

Abstract: This study was supported by the National Natural Science Foundation of China (31571545) and the Natural Science Foundation of Jiangsu Province (BK20150677). The authors have no conflict of interest to disclose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
48
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 35 publications
4
48
0
1
Order By: Relevance
“…Melatonin has important physiological functions, such as the control of circadian rhythms, decrease in oral temperature, regulation of follicular development and reproductive activity, and activation of the immune system . Previous research reports found that melatonin exerts a protective function in mouse oocytes and porcine oocytes . Our results agree with previous studies which suggest that melatonin plays an important role in steroid hormone synthesis of GCs, however, the mechanism underlying how melatonin affects steroid hormone synthesis in GCs is unclear.…”
Section: Discussionsupporting
confidence: 90%
“…Melatonin has important physiological functions, such as the control of circadian rhythms, decrease in oral temperature, regulation of follicular development and reproductive activity, and activation of the immune system . Previous research reports found that melatonin exerts a protective function in mouse oocytes and porcine oocytes . Our results agree with previous studies which suggest that melatonin plays an important role in steroid hormone synthesis of GCs, however, the mechanism underlying how melatonin affects steroid hormone synthesis in GCs is unclear.…”
Section: Discussionsupporting
confidence: 90%
“…Paraquat exposure causes abnormal distribution patterns of mitochondria in in vitro bovine oocytes, and melatonin treatment improves mitochondrial functionality of the oocytes exposed to paraquat during IVM in the bovine [42]. IVM medium supplemented with melatonin can alter mitochondrial distribution patterns of oocytes, but do not affect mitochondrial activity of bovine oocytes [43], and defective mitochondrion integrity induced by benzo(a)pyrene can be recovered by melatonin treatment via inhibiting ROS level in the porcine oocytes [34]. Therefore, melatonin can enhance mitochondrial distribution of oocytes during IVM, which is helpful for functions and development competence of in vitro oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin achieves its detoxification of reactive oxygen through inducing antioxidant enzymes [33]. Benzo(a)pyrene leads to oocyte meiotic failure, which can be recovered by melatonin supplementation through repressing ROS level in the porcine [34]. Melatonin combined with prolonged IVM enhances development of poor-quality oocytes through decreasing ROS generation in pigs [35].…”
Section: Discussionmentioning
confidence: 99%
“…This study also provides a warning for women who are frequently exposed to IBP at high concentrations by using in vitro culture model of porcine cumulus oocyte complexes as can be seen in Figure . The reason we chose porcine oocytes as a model because oocyte size and maturation time are more like human than mouse (Santos et al ), and several articles have used porcine cumulus oocyte complexes to evaluate oocyte (Liu et al ; Han et al ; Wang et al ; Miao et al ; Liang et al ).…”
Section: Discussionmentioning
confidence: 99%